Cerebrospinal Fluid IL-17A Could Predict Acute Disease Severity in Non-NMDA-Receptor Autoimmune Encephalitis - Levraut, Michael; Bourg, Véronique; Capet, Nicolas; Delourme, Adrien; Honnorat, Jérôme; Thomas, Pierre; Lebrun-Frenay, Christine (Frontiers in Immunology, 2021)
INTRODUCTION: Most of our knowledge into autoimmune encephalitis (AE) comes from N- Methyl-D-Aspartate Receptor (NMDAR) encephalitis. The concentrations of cytokines in cerebrospinal fluid (CSF) including IL-17A have been found to be increased and associated with poor outcome. However, data on the cytokine concentration in CSF and its correlation with outcome is lacking for other types of AE. OBJECTIVE: To report the concentrations of CSF sIL-2R, IL-6 , IL-8, IL-10 and IL-17A and to correlate it with acute disease severity and the 1-year outcome in non-NMDAR AE. METHODS: We measured the CSF concentration of each cytokine in 20 AE patients, and compared IL-6 and IL-17A concentrations with 13 patients with CNS demyelinating diseases and 20 non-inflammatory controls. Patients were > 18yr and had at least 1-year clinical follow- up. Intracellular and NMDAR antibody (Ab) -mediated encephalitis were excluded. A mRS ≤ 2 was retained as a 1-year good outcome. RESULTS: The IL-17A concentration in CSF was higher in AE patients than in both control groups (p<0.01). No difference was observed in CSF concentration of IL-6 between groups. At disease onset, a high CSF IL-17A concentration correlated with a high modified Rankin Scale (p<0.05), a high Clinical Assessment Scale for Autoimmune Encephalitis score (p<0.001) and ICU admission (p<0.01). There was no correlation between the concentration of all CSF cytokines and the 1-year clinical outcome. CONCLUSION: Our results show that CSF IL-17A could be interesting to assess initial severity in non-NMDAR AE. Thus, CSF IL-17A could be an interesting therapeutic target and be useful to assess early selective immunosuppressive therapy.